PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP - Noviyana, Hesti (LPPM STKIP PGRI Bandar Lampung, 2019)
Abstract: The research was carried out based on problems in the form of low students' mathematical problem solving abilities. The purpose of this study is to analyze the effect of the Make a Match type of cooperative learning model on the mathematical problem solving ability of seventh grade students of SMP. Research using quasi-experimental methods. The research population is all grade VII students of SMP Negeri 7 Bandar Lampung. Samples were taken as many as 2 classes, namely class VII.6 as an experimental class totaling 30 students, and class VII.7 as a control class totaling 29 students. The sample was taken using the Cluster Random Sampling technique with a lottery procedure. This technique is carried out, because remembering that each of the eighth grade at SMP Negeri 7 Bandar Lampung has the same average ability. The students' mathematical problem solving abilities were measured by tests in the form of a description of 5 questions. Hypothesis testing using t-test with a value of = 8,72. From the distribution table t at a significant level of 5%, it is known that means which is 8.72>2.00, so it can be concluded that there is an influence of cooperative learning models Make a Match type to the mathematical problem solving ability of VII grade students of SMP Negeri 7 Bandar Lampung.